2012
DOI: 10.5999/aps.2012.39.2.106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-rich Plasma on Wounds of OLETF Rats Using Expression of Matrix Metalloproteinase-2 and -9 mRNA

Abstract: BackgroundComplicated diabetic patients show impaired, delayed wound healing caused by multiple factors. A study on wound healing showed that platelet-rich plasma (PRP) was effective in normal tissue regeneration. Nonetheless, there is no evidence that when plateletrich plasma is applied to diabetic wounds, it normalizes the diabetic wound healing process. In this study, we have analyzed matrix metalloproteinase (MMP)-2, MMP-9 expression to investigate the effect of PRP on diabetic wounds.MethodsTwenty-four-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…PCR was performed for 40 cycles (denaturation at 95 °C for 15 s, annealing at 60 °C for 1 min and extension at 60 °C for 1 min) using a RealMasterMix Kit (SYBR Green) and a 7500 Real Time PCR System (America). The RT-PCR procedure for MMP-9 was based on a protocol described previously [20] . β-actin was used as an internal reference.…”
Section: Cell Invasion Assaymentioning
confidence: 99%
“…PCR was performed for 40 cycles (denaturation at 95 °C for 15 s, annealing at 60 °C for 1 min and extension at 60 °C for 1 min) using a RealMasterMix Kit (SYBR Green) and a 7500 Real Time PCR System (America). The RT-PCR procedure for MMP-9 was based on a protocol described previously [20] . β-actin was used as an internal reference.…”
Section: Cell Invasion Assaymentioning
confidence: 99%
“…First, cell-based method was introduced. Shin et al ( 17 ) had used platelet-rich plasma on chronic inflammatory wound, and Choi et al ( 18 ) had demonstrated the efficacy and safety of PRP (Platelet-Rich Plasma) and ADSC (Adipose-Derived Stem Cells) in chronic wound. Also Yang et al ( 19 ) reported the effect of amniotic fluid stem cells and amniotic fluid cells on the wound healing process in a white rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus Sun et al, (2010) mentioned that, PRP is a very good clinical source for osteochondral regeneration. Shin et al, (2012) proved that PRP was effective in normal tissue regeneration. But there is no clue that platelet rich plasma would normalize the diabetic wound healing pathway.…”
Section: Resultsmentioning
confidence: 98%